SOME SOLUTIONS TO THE CENTRAL ASIAN REGION’S ENERGY COOPERATION PROBLEMS - RAKHMATULINA, Gulnur (CENTRAL ASIA AND THE CAUCASUS, 2007)
It stands to reason that the resource-rich Central Asian Region (CAR), which is located at the crossroads between the Near and Middle East, South Asia, China, and Russia and is also in direct proximity to the countries experiencing “energy starvation,” is of important geostrategic significance.It is a well-known fact that CAR has vast energy potential. Kazakhstan, Turkmenistan, and Uzbekistan have large supplies of oil and gas resources, which enjoy demand on the world market. In particular, 22 raw hydrocarbon fields have been developed in Kazakhstan, particularly in the Caspian Depression and South Turgai.1The State Development Program of the Kazakhstan Sector of the Caspian Sea (KSCS) bodes well for increasing the volumes of hydrocarbon production in the republic. The forecasted reserves of this raw material in the sections and structures where work has begun alone top 2 billion tons of oil equivalent. By 2010, oil production will amount to 90 million tons and gas production to 52.5 bcm, while by 2015, these figures will have risen to 150 million tons and 79.4 bcm, respectively (according to the data of the Ministry of Energy and Mineral Resources of the Republic of Kazakhstan). In 2006, oil production reached 65 million tons, and natural gas production amounted to 27 bcm.2Kyrgyzstan and Tajikistan have unique hydropower potential. Its rational use will make it possible to supply the energy-deficit regions (including in Kazakhstan’s southern regions) with cheap electric power and water. The CAR countries also have a certain amount of potential for developing the atomic power industry. Large fields of uranium ore have been discovered in Kazakhstan, Kyrgyzstan, and Tajikistan. As one of the four largest producers of natural uranium, Kazakhstan possesses 19% of the world’s total supplies, yielding only to Australia in terms of this index.3 On the world nuclear fuel and rare metals market, Kazakhstan is represented by the Kazatomprom National Nuclear Company. Its main production, 100% of which is exported, is natural uranium, nuclear fuel for atomic power plants, and items and semi-finished products made from beryl, tantalum, niobium, and their alloys. In 2006, 5,300 tons of uranium were extracted in Kazakhstan, and by 2010, there are plans to raise its production to 15,000 tons a year.4The industry is focusing great attention on attracting foreign capital. Joint ventures have already been created with companies from Canada, France, Russia, and Japan. There are plans to engage in joint production with South Korea, the PRC, and the U.S., which, in light of the IAEA’s prediction that world resources will be exhausted by 2020, should make Kazakhstan one of the monopolists on the uranium market. This is very realistic if we keep in mind that Kazakhstan has no equals in terms of ore supplies suitable for underground leaching.